Fostering Children Who Commit Criminal Offenses In Special Child Development Institutions - Jefri Takkas Parulian Hutapea; Syaiful Asmi Hasibuan; Yasmirah (ASIAN PUBLISHER, 2024)
The Child Special Development Institution or abbreviated as LPKA is an institution where children serve their sentence, LPKA is the final stage of the criminal justice system authorized by the state to provide guidance and provide protection to correctional students who are appropriate and in accordance with the conditions of the child inmate, in the field there are still often found repeated criminal offenders, and there are children aged 19 years who are placed in LPKA. The question in this thesis is how the form of coaching for child offenders of repeated criminal offenses in LPKA Klas I Medan and what are the inhibiting and supporting factors for the coaching of children of repeated criminal offenders in LPKA Klas I Medan. In this research the author uses the Empirical Juridical research method with the aim of providing answers to researcher questions based on secondary data collected from library materials, primary data obtained from interviews and documentation and tertiary data, namely other supporting data.Religious Development such as five daily prayers, reading the Qur'an, sholawat and giving spiritual studies every Friday in collaboration with the Ministry of Religion. Educational Development named PKBM (Community Learning Activity Center), namely learning with the package system A, B and C in collaboration with the Education Office. Skills Development, namely interests and talents such as sports, arts, welding training activities, handicrafts, fisheries and agriculture. From the explanation above, it is concluded that the inhibiting factors of coaching, the absence of regulations governing children of repeat offenders specifically, a short coaching period, the completeness of facilities and infrastructure that has not been maximized, the lack of instructors / coaches to assist andik coaching activities. As for the supporting factors for coaching, all parties in LPKA take responsibility for the future of andik, good cooperation with partners to bring competent parties in their fields, the role of the surrounding community and supporting facilities and infrastructure in LPKA Klas I Medan. The Child Special Development Institution or abbreviated as LPKA is an institution where children serve their sentence, LPKA is the final stage of the criminal justice system authorized by the state to provide guidance and provide protection to correctional students who are appropriate and in accordance with the conditions of the child inmate, in the field there are still often found repeated criminal offenders, and there are children aged 19 years who are placed in LPKA. The question in this thesis is how the form of coaching for child offenders of repeated criminal offenses in LPKA Klas I Medan and what are the inhibiting and supporting factors for the coaching of children of repeated criminal offenders in LPKA Klas I Medan. In this research the author uses the Empirical Juridical research method with the aim of providing answers to researcher questions based on secondary data collected from library materials, primary data obtained from interviews and documentation and tertiary data, namely other supporting data.Religious Development such as five daily prayers, reading the Qur'an, sholawat and giving spiritual studies every Friday in collaboration with the Ministry of Religion. Educational Development named PKBM (Community Learning Activity Center), namely learning with the package system A, B and C in collaboration with the Education Office. Skills Development, namely interests and talents such as sports, arts, welding training activities, handicrafts, fisheries and agriculture. From the explanation above, it is concluded that the inhibiting factors of coaching, the absence of regulations governing children of repeat offenders specifically, a short coaching period, the completeness of facilities and infrastructure that has not been maximized, the lack of instructors / coaches to assist andik coaching activities. As for the supporting factors for coaching, all parties in LPKA take responsibility for the future of andik, good cooperation with partners to bring competent parties in their fields, the role of the surrounding community and supporting facilities and infrastructure in LPKA Klas I Medan.